2020
DOI: 10.3390/metabo10070297
|View full text |Cite
|
Sign up to set email alerts
|

hcapca: Automated Hierarchical Clustering and Principal Component Analysis of Large Metabolomic Datasets in R

Abstract: Microbial natural product discovery programs face two main challenges today: rapidly prioritizing strains for discovering new molecules and avoiding the rediscovery of already known molecules. Typically, these problems have been tackled using biological assays to identify promising strains and techniques that model variance in a dataset such as PCA to highlight novel chemistry. While these tools have shown successful outcomes in the past, datasets are becoming much larger and require a new approach. Since PCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 77 publications
(112 reference statements)
0
29
0
Order By: Relevance
“…It was observed that the types of honey samples are successfully differed from each other. Spectral-based HCA assumes that samples with similar spectral profiles are chemically related and should be assigned to a single group [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the types of honey samples are successfully differed from each other. Spectral-based HCA assumes that samples with similar spectral profiles are chemically related and should be assigned to a single group [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…CA is usually used to analyze two-way data tables, including several sizes of relationships between rows and columns [29]. Hierarchical Clustering on Principal Components (HCPC) is a combination of Hierarchical Clustering with Principal Components of the PCA model [30]. HCPC is objective grouping techniques on the results of principal component analysis, which leads to better cluster solutions [29].…”
Section: Discussionmentioning
confidence: 99%
“…In order to cluster the metabolites, principal component analysis (PCA), linear discriminant analysis (LDA) and partial least squares discriminant analysis (PLS-DA) are normally used in the R packages or other tools, such as MetaboAnalyst, VOCCluster [93,95]. Tools with new features, such as interactive time-series cluster analysis (R package MetaboClust) [96], automated hierarchical cluster (R package hcapca) [97] are also developed for clustering analysis. Bayesian network method (BNM) can model the interactions of the metabolites to identify important metabolites in the optimal network, which has been demonstrated in the study of Rogers et al (2014) [98].…”
Section: Methods and Tools Applied In Metabolomics Analysismentioning
confidence: 99%